Hands-on Learning through Technology Integration in Teacher Education: Creating Projects with Makey Makey Boards - Castro Araya , Hazel (2025)
This study, presented at the IV Primary Education Conference: Transforming Education in the Face of Current and Future Challenges examines a workshop on the use of Constructionism and a STEAM approach to create educational projects with Makey Makey equipment from the perspective of teacher trainees who participated in the workshop. The objective was to evaluate the feasibility of conducting such workshops as an effective way of promoting creative thinking and fostering technology skills for teacher training purposes. Research was based on a quantitative methodology with surveys to track project progression. Workshops were created using a Design Thinking methodology and implemented with three cohorts from a Creativity and Talent course during 2022, 2023 and 2024. Course participants were either Primary Education, English for Primary Education or Early Childhood Education majors at the Guanacaste Campus of the University of Costa Rica (UCR). Workshops were facilitated by Educational Technologies for Learning Program, PROTEA staff from the UCR Rodrigo Facio Campus in San José, Costa Rica. The factors that were analyzed include the environment and materials, the pedagogical approach, the impact of the innovation and practicality of implementing this teaching method in a classroom setting. Students evaluated the workshop favorably and expressed a strong inclination to adopt a Design Thinking methodology through Makey Makey technology together with the resources learned in the workshop for classroom projects. The workshop proved to have a positive impact on teacher training by fostering creativity, innovation and integration of new technologies. Study limitations included the sample size and absence of a control group. Expanding educational settings to implement this technology and further research for its integration in classrooms, supported by a systematic pedagogical approach is recommended.